Outlining a right of access to sanitation in South African Law - Van Zyl, Nicolas (Department of Public Law, 2017)
For many people their ease of access to a private home toilet means that when and where they go to relieve themselves is rarely a deliberation in their minds. In South Africa's rural and peri-urban spaces there are many poor people for whom this is not the case. For these people the inadequacy of their access to sanitation compromises their health, safety and ability to live a dignified life. Without an explicit right included in the Constitution, litigating on access to sanitation poses a formidable legal challenge. However, a critical analysis of South Africa's socio-economic and administrative law jurisprudence reveals that a fundamental right of access to sanitation is not exactly necessary. Outlining South Africa's vast network of service delivery legislation and policy, this thesis submits that there is a principled basis in our law to enforce a right of access to sanitation. It illustrates that this legal basis extends beyond merely protecting a person's existing access to sanitation, but includes positive duties imposed on the state to provide certain services as well.